Exploring the association between relative fat mass and psoriasis risk: insights from the NHANES data - Zeru Chen; Haiwei Chen; Xiaotong Chen; Yuling Chen; Jintong Wang; Yuhua Ou (Lipids in Health and Disease)
Abstract Background Patients' quality of life is greatly impacted by psoriasis, a prevalent chronic inflammatory skin condition that is frequently linked to a number of systemic disorders. Recent research shows that obesity is a major risk factor for psoriasis. Since Relative Fat Mass (RFM), an innovative way to measure obesity, offers a more precise estimate of body fat percentage, this study aims to investigate the connection between RFM and psoriasis and its potential as a disease predictor. Methods The analysis included 6,006 people the National Health and Nutrition Examination Survey (NHANES) conducted between 2003 and 2006, 151 of whom had psoriasis. Weighted multivariable logistic regression, restricted cubic splines (RCS), subgroup analysis, and interaction tests were employed to assess the link between RFM and psoriasis. ROC curves were used to compare RFM with conventional measures of obesity (WWI, BRI). Furthermore, LASSO regression and multivariable regression based on AIC were used to create a psoriasis risk prediction model that included RFM and additional clinical factors. Results RFM and psoriasis risk were revealed to be significantly positively correlated. The chance of developing psoriasis increased by 7% for every unit rise in RFM (95% CI: 1.03 to 1.12). RFM showed better predictive ability than conventional markers including BMI, WWI, and BRI (AUC = 0.573). The RFM-psoriasis relationship and diabetes status significantly interacted, with the association being weaker in diabetic individuals, according to subgroup analysis and interaction tests. Promising results were obtained from the created psoriasis risk prediction model that included RFM, age, total dietary sugar, education level, history of heart disease, and hypertension. Conclusion This research demonstrates that RFM outperforms traditional anthropometric methods in predicting risk. It also presents the initial evidence establishing a positive link between RFM and the likelihood of developing psoriasis.The psoriasis risk prediction model underscores RFM's effectiveness as a valuable approach in both clinical and public health domains, aiming to alleviate the impact of psoriasis-related issues by offering a practical instrument for early risk assessment and personalized clinical strategies.